Antioxidant potential of Amazonian plants: An integrative review (Revista Contexto & Saúde, 2025)
Objective: review the scientific literature that addresses the antioxidant capacity of Amazon plants. Methods: This is an integrative review in English language papers carried out on PubMed/MEDLINE, in the period from 2002 to 2022. Results: The search resulted in 21 eligible papers in which 24 plants with antioxidant capacity were identified, distributed in 15 families. It was found that the studies do not have a standardized methodology, which makes it difficult to compare between plants. Despite this, it was possible to define the Myrtaceae and Lauraceae families as those that have plant species with the highest antioxidant potential, with Psidium guajava (32000 µmol TE/g) and Aniba canelilla (1.8ppm) being their representatives with the highest potential, respectively. Conclusion: A diversity of Amazonian plants with antioxidant potential was observed in different botanical families. The analysis of studies points to phenolic compounds, such as flavonoids, tannins, chromones, FAE and quercetin, as principal determinants for these species to have this antioxidant capacity. Future developments in this line of research include more studies with the plants with the highest antioxidant capacity with a focus on the analysis of the chemical constituents that make up the samples of the Amazonian plants.
Keywords: Plantas; Ecosistema amazónico; antioxidantes